A meta‐analysis comparing first‐line immunosuppressants in neuromyelitis optica. Issue 10 (10th September 2021) - Giovannelli, Jonathan; Ciron, Jonathan; Cohen, Mikael; Kim, Ho‐Jin; Kim, Su‐Hyun; Stellmann, Jan‐Patrik; Kleiter, Ingo; McCreary, Morgan; Greenberg, Benjamin M.; Deschamps, Romain; Audoin, Bertrand; Maillart, Elisabeth; et al.
Abstract: Objective: As phase III trials have shown interest in innovative but expensive drugs in the treatment of neuromyelitis optica spectrum disorder (NMOSD), data are needed to clarify strategies in the treatment of neuromyelitis optica (NMO). This meta‐analysis compares the efficacy of first‐line strategies using rituximab (RTX), mycophenolate mofetil (MMF), or azathioprine (AZA), which are still widely used. Methods: Studies identified by the systematic review of Huang et al. (2019) were selected if they considered at least two first‐line immunosuppressants among RTX, MMF, and AZA. We updated this review. The Medline, Cochrane Central Register of Controlled Trials, Embase, and ClinicalTrials databases were queried between November 2018 and April 2020. To be included, the hazard ratio (HR) [95% CI] for the time to first relapse after first‐line immunosuppression had to be available, calculable, or provided by the authors. Results: We gathered data from 919 NMO patients (232 RTX‐, 294 MMF‐, and 393 AZA‐treated patients). The risk of first relapse after first‐line immunosuppression was 1.55 [1.04, 2.31] ( p = 0.03) for MMF compared with RTX, 1.42 [0.87, 2.30] ( p = 0.16) for AZA compared with RTX, and 0.94 [0.58, 1.54] ( p = 0.08) for MMF compared with AZA. Interpretation: The findings suggest that RTX is more efficient than MMF as a first‐line therapy. Even if the results of our meta‐analysis cannot conclude that RTX has a better efficacy in delaying the first relapse than AZA, the observed effect difference between both treatments combined with the results of previous studies using as outcome the annualized relapse rate may be in favor of RTX.